Foot soak device to improve sleep quality for pregnant women - Afriannisyah, Entan; Syafitasari, Juanda; Putri, Poppy Siska (Institute of Computer Science (IOCS), 2024)
The study explores the development of a Foot Soak Device to improve the sleep quality of pregnant women in their third trimester. Pregnant women often experience discomfort such as leg edema, back pain, and sleep disturbances due to increased fetal weight, shortness of breath, and fetal movements. Poor sleep quality can negatively impact health, weaken the immune system, and lead to complications like low birth weight in newborns. Existing foot soak devices lack key features such as temperature regulation, heating, and massage, prompting researchers to innovate a new foot soak device tailored to pregnant women. The research follows a Research and Development (R&D) method. It includes two stages: the first involves analysis and product development based on feedback from five third-trimester pregnant women, while the second stage tests the product’s efficacy through a quasi-experimental design with a one group pretest-posttest involving 20 pregnant women, using purposive sampling. Results from the first stage highlighted the need for a foot soak with temperature control, a heater, and massage functionality. The developed device incorporated these features, and 90% of participants found the foot soaks comfortable. In the second phase, the analysis showed a significant effect of the foot soak on improving sleep quality (p ≤ 0.05). The study concludes that midwives could implement this foot soak device as part of midwifery care to enhance the quality of life for pregnant women in the third trimester.